Arshak Chopanian and the “Anahit” Journal in the Origins of Komitas Studies - Asatryan, Anna (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
The Armenian writer, critic, linguist, journalist and public figure Arshak Chopanian’s (1872–1954) role in the creative life of Komitas is exceptional, and significant is his contribution to the formation of Komitas studies. Komitas and A. Chopanian‘s acquaintance took place in Paris in July 1901 and lasted through Komitas’ death. A. Chopanian did not only highly appreciate Komitas’s talent and the work he did, but also attached importance to creating favorable conditions for his activity and took a lot of practical steps to that end. In Anahit, the literary, artistic and public magazine founded by him in Paris in 1898, as well as in other periodicals of the time, such as Byuzandion (Constantinople), Hayastani kochnak [Armenia’s Bell] (New York), etc., A. Chopanian placed articles, in which he commended Komitas’ activity, thereby making his works known to broader public. On the pages of Anahit, A. Chopanian, on the one hand, presented the full-fledged panorama of Komitas’ concert activities that unfolded in Paris and Geneva, published materials assessing Komitas’ oeuvre, authored by various musicians, as well as memoirs, and, on the other, Komitas’ own studies in musicology and a piece of his literary legacy – his autobiography. A. Chopanian’s Komitassiana had had also applied significance. Several important issues raised by A. Chopanian – in particular, the issue of burying Komitas in Armenia, and that of publishing his musical legacy – were brought to life in the near future. Բացառիկ է հայ գրող, քննադատ, բանասեր, լրագրող և հասարակական գործիչ Արշակ Չոպանյանի (1872–1954) դերը Կոմիտասի ստեղծագործական ճակատագրում, ծանրակշիռ նրա ներդրումը՝ կոմիտասագիտության ձևավորման գործում։ Կոմիտասի և Ա․ Չոպանյանի ծանոթությունը տեղի ունեցավ Փարիզում՝ 1901 թվականի հուլիսին և շարունակվեց մինչև Կոմիտասի մահը։ Ա. Չոպանյանը ոչ միայն բարձր է գնահատել Կոմիտասի տաղանդն ու նրա կատարած գործը, այլև կարևորել նրա գործունեության համար նպաստավոր պայմաններ ստեղծելու անհրաժեշտությունը՝ այդ ուղղությամբ կատարելով բազմաթիվ գործնական քայլեր: 1898-ին Փարիզում իր ստեղծած «Անահիտ» գրական, գեղարվեստական, հասարակական հանդեսում և ժամանակի պարբերական մամուլում (այդ թվում՝ «Բիւզանդիոն» (Կ. Պոլիս), «Հայաստանի կոչնակ» (Նյու Յորք) և այլն) հրատարակած իր հոդվածներում Չոպանյանն արժևորել է Կոմիտասի գործունեությունը և նպաստել նրա ստեղծագործության պրոպագանդմանը: «Անահիտ»-ի էջերում Ա. Չոպանյանը մի կողմից՝ ներկայացրել է Փարիզում և Ժնևում Կոմիտասի ծավալած համերգային գործունեության լիարժեք համայնապատկերը, տպագրել տարբեր երաժիշտների կողմից Կոմիտասին նվիրված հոդվածներն ու գնահատականները, էջեր հատկացրել հուշագրություններին, մյուս կողմից՝ հրատարակել Կոմիտասի երաժշտագիտական ուսումնասիրությունները և գրական ժառանգության էջերից մեկը՝ Կոմիտասի ինքնակենսագրությունը: Ա. Չոպանյանի կոմիտասականը ունեցել է նաև կիրառական նշանակություն. նրա առաջ քաշած մի շարք կարևոր հարցեր, այդ թվում՝ Կոմիտասին Հայաստանում յաստանում հուղարկավորելու և նրա երաժշտական ժառանգությունը հրատարակելու հարցերն իրականություն դարձան մոտ ապագայում։
Keywords: Art; Armenian press